Sistem Informasi Penelitian Dosen Pada Lp2m Itb Asia Malang Berbasis Web - Achlul Nizar; Lilis Widayanti (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2023)
LP2M is an institution that manages research activities and the implementation of community service by lecturers at a tertiary institution. The process of research and implementation of community service is carried out in the order of sending proposals, evaluating them, and determining whether they are accepted or not. In this case the problem found is the lack of efficiency in documenting lecturer research data. At the ITB Asia Malang, LP2M already has procedures in submitting research and community service. However, the process is still manual or not systematic in its implementation because researchers send proposals via email. The weakness faced is that it is difficult to read any proposal document or report. The author intends to build a web-based application as a forum for tidying up documents on lecturer research activities at ITB Asia Malang. The process of receiving and selecting proposals through information technology must be improved. The final result of this research is an information system application for research by ITB Asia Malang lecturers that was built using the PHP programming language and data processing with MySQL. This system has been tested and it can be concluded that the features in the system have functioned as needed.